On the possibility of obtaining the elastic and biocompatible film materials based on chitosan and N-succinyl chitosan - Marina V. Bazunova; Roman Yu. Lazdin; Mariya R. Elinson; Lucia A. Sharafutdinova; Robert A. Mustakimov; Elena I. Kulish (Chimica Techno Acta)
For the first time, the studies of polyhydric alcohols (glycerol, ethylene glycol and propylene glycol) impact on the structure, deformation–strength characteristics and hemocompatibility of the film materials based on chitosan and N-succinyl chitosan were carried out. It was shown that the introduction of polyhydric alcohols into molding solutions during the creation of the films based on chitosan and succinyl chitosan in the amount up to 0.05 mol/l is accompanied by the tensile elongation value increase by 2–2.5 times. The value of the breaking stress in this case decreases by 3–4 times. There is also a decrease in the overall surface roughness and a sharp drop in the elastic modulus of the films. The stabilizing impact of the systems based on chitosan and succinyl chitosan in the presence of glycerol and propylene glycol upon the cell membranes in physiological conditions allows inferring their high hemocompatibility.